2019
DOI: 10.54987/jemat.v7i1.468
|View full text |Cite
|
Sign up to set email alerts
|

Arrhenius Plot Analysis, Temperature Coefficient and Q10 Value Estimation for the Effect of Temperature on the Growth Rate on Acrylamide by the Antarctic Bacterium Pseudomonas sp. Strain DRYJ7

Abstract: Several models are available to model the effect of temperature on the growth rate of microorganism on substrates. One of the models is Arrhenius and is very popular due to it having few parameters. An apparent activation energy based on the Arrhenius plot on the growth on acrylamide by Pseudomonas sp. strain DRYJ7 on acrylamide is reported for the first time. The bacterium was grown in minimal salts media supplemented with 1000 mg/L of acrylamide as a nitrogen source and glucose as the carbon source. The plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 0 publications
0
17
1
Order By: Relevance
“…[25] whereas a Q10 value of 2.17 was determined to be appropriate for the growth rate of this organism when fed diesel. In another study on the biodegradation of acrylamide, the Q10 value was reported to be 2.17, which is lower [21] According to our calculations (Fig. 3), the theta value of the bacterium's molybdenum reduction was equivalent to that of our previous theta value estimate of 1.08 for Serratia sp.…”
Section: Resultscontrasting
confidence: 51%
See 4 more Smart Citations
“…[25] whereas a Q10 value of 2.17 was determined to be appropriate for the growth rate of this organism when fed diesel. In another study on the biodegradation of acrylamide, the Q10 value was reported to be 2.17, which is lower [21] According to our calculations (Fig. 3), the theta value of the bacterium's molybdenum reduction was equivalent to that of our previous theta value estimate of 1.08 for Serratia sp.…”
Section: Resultscontrasting
confidence: 51%
“…strain DRYJ7 grew at a rate of 1.03 on acrylamide, according to a study. Theta was found to be a value of 1.03 [21]. There have been reports of xenobiotic degradation theta values as high as 16.2, however the theta value here is between 1.1 and 1.7, which is common for many biological processes [55].…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations